Self-contained polymer/metal 3D printed electrochemical platform for tailored water splitting - Ambrosi, Adriano (2019)
The enormous advancements made recently in additive manufacturing require parallel development of new printable materials with particular focus on so‐defined functional materials. Functional materials have specific properties that are useful for the fabrication of active devices such as sensors, electronic components, catalytic reactors, etc. It is shown here that the combination of standard 3D‐printing technologies with easy‐to‐use electrochemical surface modification can facilitate the tuning of catalytic properties of printed metallic electrodes to be used as electrocatalysts for water splitting applications. A self‐contained electrochemical system, consisting of electrodes and an electrochemical cell, is built via 3D metal and polymer printing. Stainless‐steel electrodes are first obtained by selective laser melting additive manufacturing according to an established design; then electrochemical surface modification is performed to alter the electrode surface composition and therefore tune its catalytic properties toward the electrogeneration of hydrogen and oxygen. After surface characterization by means of scanning electron microscopy in combination with energy dispersive X‐ray microanalysis to evaluate the efficiency of the electrochemical functionalization, electrochemical testing is carried out to evaluate the catalytic properties of the electrodes. A simple, proof‐of‐concept water electrolyzer is finally assembled with the best performing electrodes and tested in alkaline solution for water splitting capabilities.